METHODOLOGY OF ORGANIZATION OF MIDDLE RUNNING TRAINING IN ATHLETICS: Preschool and Primary Education of - Ochilov, Navro'zbek (Maktabgacha taʼlim jurnali, 2021)
The article examines the types and processes of practical training in middle distance running by the type of athletics. The processes of practical training of middle distance runners and the forms of organizing practical classes are, analyzed. Discussions were, also held on the methods and principles of improving technical and tactical skills, the development of physical qualities, which are the main goals and objectives of practical training of middle-distance runners.